POTENSI ANTIBAKTERI TIGA SPESIES BAKTERI ASAM LAKTAT ASLI ENGGANO TERHADAP BAKTERI PATOGEN DAN PEMBUSUK MAKANAN [Antibacterial Potential of Three Indigenous Lactic Acid Bacteria Species from Enggano Against Pathogenic and Food Spoilage Bacteria] - sulistiani, sulistiani; Khusniati, Tatik (BERITA BIOLOGI, 2016)
Lactic acid bacteria (LAB) strains have been known for their antimicrobial compounds that are important for food industry,including extension of expired time for food products. In this study, LAB isolates were isolated anaerobically from coconut sap using MRSA medium. Antibacterial analysis was carried out using microdilution method on microplate. The antibacterial assay showed that 85 isolates of LAB exhibit antibacterial activities against Escherichia coli, Salmonella enterica, Staphylococcus aureus, Pseudomonas aeruginosa, Listeria monocytogenes, and Bacillus cereus. Molecular identification of 13 physiologically characterized LAB strains based on 16S rDNA sequence determined three species, namely, Leuconostoc mesenteroides (strain EN17-1, EN17-8, EN17-12, EN17-15, EN17-34, EN17-41, EN17-43, EN17-45, EN17-46, EN38-34), Lactobacillus fermentum (strain EN17-2, EN38-44) and L. satsumensis strain EN38-32. The strong and wide broad spectrum antibacterial activity was produced by L. satsumensis strain EN38-32.Â